Empowerment and sustainability of small and medium Department of Tourism (DOT) accredited restaurants in Calabarzon - Frias-dela Cruz, Barbara F.; Ma. Linda R. Fernandez
"This study aimed to evaluate the organizational efficiency of food businesses in the CALABARZON region, focusing on marketing, financial management, production/operations, and human resources. It also assessed the financial performance of these businesses in terms of liquidity, profitability, efficiency, and leverage, identified challenges affecting efficiency, and proposed a strategic organizational model to enhance performance and sustainability. The study was limited to food corporations operating casual restaurants for at least five years. Out of eight corporations invited, five agreed to participate, representing Cavite, Laguna, Batangas, Rizal, and Quezon. A descriptive-correlational research design using a mixed-methods approach was employed. Stratified purposive sampling resulted in 169 respondents composed of five owners/managers and 164 employees. Data were gathered through validated survey instruments, interviews, and financial document analysis. Appropriate statistical tools determined the differences and relationships between organizational efficiency and financial performance. Findings revealed that food businesses were generally rated as *Very Much Efficient,"" with high efficiency in marketing and financial management, and slightly lower ratings in human resources. No significant difference was observed in organizational efficiency when respondents were grouped according to profile. Financial performance showed improved liquidity but decreasing profitability and leverage ratios, indicating potential risks to long-term stability. Results showed a strong positive relationship between production/operational and financial efficiency and financial performance, while marketing and human resources had indirect effects. Identified challenges included customer retention, market competition, staff training, compliance with regulations, and technology adoption. The study concludes that internal operational practices are critical in driving efficiency. It recommends strengthening financial systems, enhancing HR development, leveraging technology, and adopting targeted marketing strategies. A Strategic Organizational Efficiency Model was proposed to serve as a framework for improving performance and ensuring sustainability. Keywords: Organizational Efficiency, Financial Performance, Food Businesses, CALABARZON, Marketing, Human Resources, Production Operations "
Dissertation